Origin of orthopyroxene-bearing felsic gneiss from the perspective of ultrahigh-temperature metamorphism: an example from the Chilka Lake migmatite complex, Eastern Ghats Belt, India. (17th October 2020) - Bose, Sankar; Das, Kaushik; Torimoto, Junji; Dunkley, Daniel
Abstract: Orthopyroxene-bearing felsic gneiss occurs as foliation-parallel layers and bands together with aluminous granulite, mafic granulite, and quartzofeldspathic granulite in the Chilka Lake migmatite complex of the Proterozoic Eastern Ghats Belt, India. The rock was classified previously as charnockite which underwent granulite-facies metamorphism. Field and textural features of this rock show evidence of the partial melting of a biotite-bearing greywacke protolith. Orthopyroxene with/without garnet and cordierite were produced with K-feldspar as peritectic phases of incongruent melting of presumed metaluminous sediments. Fluid-inclusion data suggest the presence of high-density CO2 -rich fluids during peak metamorphism, which are similar to those found in associated aluminous granulite. Whole-rock major and trace element data show wide variability of the source materials whereas REE distributions show enriched LREE and flat HREE patterns. Zircon grains from representative samples show the presence of inherited cores having spot dates (SHRIMP) in the range c. 1790–3270 Ma. The overgrowth on zircon was formed predominantly during c. 780–730 Ma and sporadically during c. 550–520 Ma. Some neoblastic zircons with c. 780–730 Ma ages are also present. U-rich dark zones surrounding cores appear partially metamictised, but spot ages from this zone vary within c. 1000–900 Ma. The <1000 Ma ages represent metamorphism that mirrors the events in associated aluminous granulite. The sources of metaluminous sediments are speculative as the rock compositions are largely modified under granulite-facies metamorphism and partial melting. Considering the accretionary tectonic setting of the Eastern Ghats Belt during the c. 1000–900 Ma time frame, a greywacke-type protolith for the migmatite complex has been proposed.